PERANAN FILSAFAT ILMU DALAM PENDIDIKAN PANCASILA - Devi Ariani; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Bajang Institute, 2022)
Pancasila values have a very important role for adolescents who are in the process of self-discovery and the formation of moral coaching. This study employs the Literature Review method.Pancasila's rolewith the education system is reviewed by axiological philosophy, it can be explained that Pancasila is a guide to the life of the Indonesian nation which contains values as a reference in living life and life. Successful civic education will cultivate and form good citizens and form behaviors in accordance with the values of Pancasila: 1. Have faith and piety in God Almighty, and live the philosophy of the nation 2. Virtuous character, discipline in the life of the nation and state. Be national, dynamically carry out the duties of rights and obligations in state life.